Tindak Pidana Pembunuhan dengan Mutilasi dalam Hukum Pidana di Indonesia - Ahmad; Zulkifli Ismail; Melanie Pita Lestari (KRTHA BHAYANGKARA, 2022)
Mutilation is an act that causes the victim to die by taking the life and then dismembering the victim's body. This mutilation has the aim of eliminating traces of the murder. The Criminal Code Articles 338 and 340 serve as the basis for imposing sentences for the perpetrators of the crime of mutilation, but these two articles do not regulate and explain in detail about mutilation. Because there is no regulation that specifically regulates mutilation killings, the perpetrators of mutilation are subject to the same articles as those of ordinary murder and premeditated murder. Therefore, the problem that will be discussed in this paper is how the crime of murder by mutilation is in criminal law in Indonesia. The research method used is a normative juridical method using a statutory approach and a case approach. The results of the research obtained are that the crime of murder by mutilation gets special arrangements in the legislation so that there are special differences for the perpetrators so that they can provide protection and a sense of security to the community.